Ear reproductive development components associated with kernel set in maize: breeding effects under contrasting environments - Rossini, María (2023)
Context or problem: Kernel number per ear (KNE) is the main driver of improved grain yield per ear (GYE) in maize (Zea mays L.). Under non-limiting conditions, KNE responded to variations in ear developmental traits such as the number of completely developed florets (CDFE) and exposed silks per ear (ESE), which have been positively affected by breeding. This trend needs to be assessed under common abiotic constraints that usually affect rainfed maize production. Objective or research question: The aim of the current research was to study breeding effects on maize grain yield and its associated reproductive developmental traits as well as the sources of loss of kernel number under a wide range of growing conditions per plant. Methods: Field experiments were conducted at two sites of the Central Pampas of Argentina, where hybrids of different year of release (from 1980 to 2012) were evaluated under 10 managed environments generated by the combination of (i) three growing seasons (2015–16: S1; 2017–18: S2; 2018–19: S3), (ii) two nitrogen rates (N0: no nitrogen added; N200: 200 kg N ha-1), and (iii) two stand densities in S1 and S2 (9 and 12 plants m-2). Plant biomass at R1 was used as a classifier of pre-flowering growth conditions (LOW, MID-LOW, MID-HIGH, and HIGH environments). Results: Although modern hybrids always presented more GYE and KNE than old hybrids, the reproductive developmental processes behind this response were different depending on the environment. Under HIGH en vironments, the KNE improvement (4.53 kernels year-1) was the result of a greater CDFE (7.55 florets year-1) and more ESE (6.01 silks year-1). Under LOW environments, the genetic progress in KNE (2.41 kernels year-1) was associated with a reduced kernel abortion (− 0.48 % year-1). Non-significant trend with year of release was observed in spikelet growth rate in all groups of evaluated environments, however, there was a significant decrease in the residual effect of the relationship between spikelet growth rate during the critical period and kernel abortion under LOW environments. Conclusions: Traits responsible for improved grain yield differed across environments because the relative importance of the determinant processes of kernel set vary across them. Under low-yielding environments, decreased kernel abortion is more beneficial than increased potential ear size (i.e., florets per ear) to enhance kernel number and grain yield. Implications or significance: This finding highlights the relevance of focusing on processes conducive to kernel abortion under stress-prone environments to improve maize grain yield.